R wave amplitude during exercise. Relation to left ventricular function and coronary artery disease - Baron, D W; Ilsley, C; Sheiban, I; Poole-Wilson, P A; Rickards, A F (British Heart Journal, 1980)
Change in R wave amplitude (mean delta R) was measured sequentially during and after 12 lead maximal treadmill exercise tests in 14 subjects with normal coronary arteries and 62 patients with coronary artery disease. In normal subjects mean delta R decreased maximally one minute after exercise and returned to control levels within three minutes. In contrast, mean delta R increased in patients with coronary artery disease, the greatest change occurring in patients with either triple vessel or left main disease or those with an akinetic region on the left ventriculogram. R wave amplitude returned to resting levels in five minutes. Increase in R wave amplitude was not directly related to changes in the ST segment. Changes in R wave amplitude during maximal treadmill exercise may improve the discrimination between patients with and without coronary artery disease and may help to identify those patients with abnormal left ventricular function.